2014
DOI: 10.1371/journal.pone.0087684
|View full text |Cite|
|
Sign up to set email alerts
|

BRK Targets Dok1 for Ubiquitin-Mediated Proteasomal Degradation to Promote Cell Proliferation and Migration

Abstract: Breast tumor kinase (BRK), also known as protein tyrosine kinase 6 (PTK6), is a non-receptor tyrosine kinase overexpressed in more that 60% of human breast carcinomas. The overexpression of BRK has been shown to sensitize mammary epithelial cells to mitogenic signaling and to promote cell proliferation and tumor formation. The molecular mechanisms of BRK have been unveiled by the identification and characterization of BRK target proteins. Downstream of tyrosine kinases 1 or Dok1 is a scaffolding protein and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 88 publications
1
15
0
Order By: Relevance
“…Cancer cells with degradation of DOK1 by BRK acquire more aggressive phenotypes. 32. TM4SF4, a member of the tetraspanin L6 domain family, has been reported to be overexpressed in radiation-resistant lung cancer cells 33.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells with degradation of DOK1 by BRK acquire more aggressive phenotypes. 32. TM4SF4, a member of the tetraspanin L6 domain family, has been reported to be overexpressed in radiation-resistant lung cancer cells 33.…”
Section: Discussionmentioning
confidence: 99%
“…No previous studies have examined the effect of FRK activation on its tumor suppressor function. We have previously shown that the constitutively active variant of BRK significantly promoted the oncogenic properties of the enzyme [ 28 , 31 ]. Stable overexpression of FRK in the Basal B/FRK-negative MDA-MB-231 breast cancer cell line resulted in reduced cell proliferation, migration, invasion, and colony formation.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of FL p62 DOK1 as a tumor suppressor is a common event in human cancers, including solid tumors ( Berger et al, 2010 , Saulnier et al, 2012 ). Oncogenic kinases ( Janas and Van Aelst, 2011 , Miah et al, 2014 ) and viruses ( Siouda et al, 2014 ) facilitate proteasomal degradation of DOK1 and epigenetic silencing of the DOK1 gene. In contrast, agents that promote stress responses (such as E2F) ( Siouda et al, 2012 ) and differentiation, e.g.…”
Section: Introductionmentioning
confidence: 99%